Răspunsuri

Cel mai inteligent răspuns!
2014-11-05T18:08:07+02:00
=( \frac{8}{15} + \frac{3}{10}):(- \frac{14}{15})+(- \frac{2}{9}+ \frac{1}{12}):(- \frac{5}{9})

= \frac{-8*2+3*3}{30}*(- \frac{15}{14})+ \frac{-2*4+3}{36}*(- \frac{9}{5})

= \frac{-16+9}{30}*(- \frac{15}{14})+ \frac{-8+3}{36}*(- \frac{9}{5})

= \frac{-7}{30}*(- \frac{15}{14})+ \frac{-5}{36}*(- \frac{9}{5})

= \frac{7}{30}* \frac{15}{14}+ \frac{5}{36}* \frac{9}{5}

= \frac{1}{4}+ \frac{1}{4}

= \frac{2}{4}

= \frac{1}{2}
sper sa te ajute.daca nu intelegi ceva ma poti intreba
multumesc mult!
cu placere